LBM-LES modelling of low-Reynolds number turbulent flow over NACA0012 aerofoil - Nadim, Nima; Chandratilleke, Tilak; Krause, M. (Springer Berlin Heidelberg, 2016)
Contemporary evolution of numerical methods in fluid dynamics includes a growing application of lattice Boltzmann modelling (LBM) for turbulent flows. Large eddy simulation, implemented on LBM framework, is established as a competent alternative for the finite volume turbulence modelling method owing to enhanced feasibility of parallelism and the transient nature of LBM equations. This work utilises a simple Smagorinsky SGS model to investigate fundamental characteristics of a turbulent flow over NACA0012 aerofoil for a range of low Reynolds number in a turbulent flow.